Juxtaglomerular cell tumor: report of a case with unusual presentation - Priscilla Quach; Ameer Hamza (Autopsy and Case Reports, 2022)
Juxtaglomerular cell tumor is a benign, renin-secreting neoplasm. The tumor arises from the juxtaglomerular apparatus cells of the kidney. Because the tumor is hormonally active, patients usually suffer from hypokalemia, hyperaldosteronism, and hypertension. Herein, we describe a case of a 19-year-old Asian female with a somewhat unusual presentation. A 19-year-old Asian female presented with upper extremity weakness, numbness, and tingling. On physical examination, the only notable finding was hypertension. Extensive workup revealed elevated aldosterone level and plasma renin activity. CT scan of the abdomen revealed a 2.2 cm mass in the lower pole of the left kidney. The mass was resected by partial nephrectomy. On microscopic evaluation, the tumor had glomoid appearance with sheets of uniform, round to polygonal cells with clear to eosinophilic cytoplasm. Immunohistochemical stains showed the tumor cells to be positive for CD117, CD34 and CD10 and negative for ER, PR, CK7, PAX-8, pan-cytokeratin, EMA, S100, Melan-A, HMB45, SMA and CAIX. Diagnosis of Juxtaglomerular cell tumor was rendered. This case highlights the importance of a regular physical exam and a high index of suspicion in patients presenting with unusual complaints.